In silico analysis of lipopolysaccharide and Î²-1, 3-glucan binding protein (LGBP) gene from the haemocytes of Indian white shrimp Fenneropenaeus indicus - Sivakamavalli, J.; Vaseeharan, B.; Shanthi, S.; Prabhu, N.M.; Manikandan, R.; Ravi, C.; Anand, T. Prem (Research in Biotechnology, 2012)
Lipopolysaccharide and Î²-1,3-glucan binding protein (LGBP) gene are involved in the pattern recognition mechanism of invertebrates, it induces the cell and humoral mediated immune responses like encapsulation, phagocytosis, nodule formation, clotting, synthesis of antimicrobial peptides and activation of the prophenoloxidase (proPO) system. The current study focuses to model the three-dimensional structure of novel immune related gene LGBP from the Indian white shrimp Fenneropeneaus indicus (F.indicus) by in silico homology modeling and its motif prediction. Fenneropeneaus indicus lipopolysaccharide and Î²-1,3-glucan binding protein (Fein-LGBP) consists of glycosylated regions which come under the glucanase family. Two conserved putative integrin-binding motif (cell adhesion sites), bacterial glucanase motif (GM) and two polysaccharide recognition motifs for the polysaccharide binding motif (PsBM) and Î²- glucan recognition motif (Î²-GRM) were conserved in the novel sequences of Fein-LGBP. Prediction of motifs, patterns, disulfide bridges and secondary structure were performed for functional characterization of the Fein-LGBP. Three dimensional structure of the Fein-LGBP was generated by Modeller9V8, Swiss Model and validated using NIH server. Results revealed that the modelled structure of Fein-LGBP was 75.7% of residues in allowed region. Theoretical model of Fein- LGBP facilitates to the discovery of new synthetic immune related peptides, agonists that could be useful toÂ  understand the mechanism of LGBP involvement in the prophenoloxidase activating system of crustaceans. The tertiary structure prediction of the immune related gene Fein- LGBP will assist to explore more knowledge in immune system of crustaceans.